Clinical Course of Amyloid A Amyloidosis Secondary to Rheumatoid Arthritis Treated with Anti-Rheumatic Drugs Including Biologic Agent: Case Series in Answer Cohort - Hirano, Toru; Maeda, Yuichi; Ebina, Kosuke; Nagai, Koji; Son, Yonsu; Amuro, Hideki; Hara, Ryota; Hashimoto, Motomu; Kumanogoh, Astushi (Archives of Clinical and Medical Case Reports, 2019)
Systemic amyloid A (AA) amyloidosis secondary to rheumatoid arthritis (RA) is a serious complication, often leading to end-stage renal disease (ESRD) or death. Intervention with biologic agent, which has brought a paradigm shift in the treatment of RA, may improve the prognosis of AA amyloidosis. Among RA patients in ANSWER Cohort in Japan, 11 patients with biopsy-proven AA amyloidosis were identified and retrospectively investigated. Median age at the diagnosis of AA amyloidosis was 64 years and median disease duration of RA was 16 years. ESRD occurred in 5 patients, and 3 of them died. Seven patients received the treatment with biologic agents. Poor prognosis such as ESRD or death was associated with advanced renal dysfunction, insufficient anti-inflammatory treatment and longer disease duration of RA, whereas good prognosis was associated with no renal involvement or mild renal dysfunction, and the use of biologic agents. This observation, along with presentations of all identified cases, suggests the importance of disease control during mild kidney damage using potent anti-inflammatory drug such as biologic agent to improve prognosis..